Does the Girl Next Door Affect Your Academic Outcomes and Career Choices? - Sofoklis Goulas; Rigissa Megalokonomou; Yi Zhang (Institute of Labor Economics (IZA), 2018)
Gender peer effects are potentially important for optimally organizing schools and neighborhoods. In this paper, we examine how the gender of classmates and neighbors affects a variety of high school outcomes and choice of university major. Given that students are assigned to schools based on proximity from their residential address, we define as neighbors all same-cohort peers who attend any other school within a 1-mile radius of one's school. To control for potentially confounding unobserved characteristics of schools and neighborhoods that might be correlated with peer gender composition, we exploit within-school and -neighborhood idiosyncratic variation in gender composition share across consecutive cohorts in the 12th grade. Using data for the universe of students in public schools in Greece between 2004 and 2009, we find that a higher share of females in a school or neighborhood improves both genders' subsequent scholastic performance, increases their university matriculation rates, renders them more likely to enroll in an academic university than a technical school, and affects their choice of university study. In addition, we find that only females are more likely to enroll in STEM degrees and target more lucrative occupations when they have more female peers in school or neighborhood. Based on our back-of-the-envelope calculations, a 10 percentage point increase in the proportion of females in a school or neighborhood reduces the gender gap in STEM enrollments by 2% and 3%, respectively. We also find that (1) neighborhood peer effects are as large as school peer effects, and (2) the effects are nonlinear-namely, the effects are larger for school and neighborhood cohorts with a large majority of female peers.
Keywords: J24; J21; J16; I24; 330; gender peer effects; neighborhood effects; STEM university degrees